Answered

Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

ax+by=1
bx-ay=a+b
solve in linear equation in 2 variables


Sagot :

pepe11
ax+by=1
bx-ay=a+b
The solution in attached file
View image pepe11
[tex]\left\{\begin{array}{ccc}ax+by=1&/\cdot a\\bx-ay=a+b&/\cdot b\end{array}\right\\\\+\left\{\begin{array}{ccc}a^2x+aby=a\\b^2x-aby=ab+b^2\end{array}\right\\------------\\.\ \ \ \ \ a^2x+b^2x=a+ab+b^2\\.\ \ \ \ \ \ (a^2+b^2)x=a+ab+b^2\\.\ \ \ \ \ \ \ \ \ \ \ \ x=\frac{a+ab+b^2}{a^2+b^2}\\\\a\cdot\frac{a+ab+b^2}{a^2+b^2}+by=1\\\\\frac{a^2+a^2b+ab^2}{a^2+b^2}+by=1\\\\by=1-\frac{a^2+a^2b+ab^2}{a^2+b^2}[/tex]

[tex]by=\frac{a^2+b^2}{a^2+b^2}-\frac{a^2+a^2b+ab^2}{a^2+b^2}\\\\by=\frac{a^2+b^2-a^2-a^2b-ab^2}{a^2+b^2}\\\\by=\frac{b^2-a^2b-ab^2}{a^2+b^2}\\\\y=\frac{b^2-a^2b-ab^2}{a^2b+b^3}[/tex]

[tex]y=\frac{b(b-a^2-ab)}{b(a^2+b^2)}\\\\y=\frac{b-a^2-ab}{a^2+b^2}\\\\Answer:\\\\x=\frac{a+ab+b^2}{a^2+b^2}\ and\ y=\frac{b-a^2-ab}{a^2+b^2}[/tex]